2018
DOI: 10.1074/jbc.m117.811315
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress responses in mouse models of Alzheimer's disease: Overexpression paradigm versus knockin paradigm

Abstract: Endoplasmic reticulum (ER)stressWe conclude that the role of ER stress in AD pathogenesis needs to be carefully addressed in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 39 publications
9
59
0
Order By: Relevance
“…We measured the mRNA and protein level of several markers involved in the UPR branches in human from three different diseases related to tau pathology and found that tau pathology is not associated with UPR activation. This study utilizing human samples is consistent with a growing number of studies that do not report UPR in experimental models of chronic neurodegeneration [18,19].…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…We measured the mRNA and protein level of several markers involved in the UPR branches in human from three different diseases related to tau pathology and found that tau pathology is not associated with UPR activation. This study utilizing human samples is consistent with a growing number of studies that do not report UPR in experimental models of chronic neurodegeneration [18,19].…”
Section: Introductionsupporting
confidence: 88%
“…The UPR involvement in tau-related pathology was previously questioned and investigated and of note, no indication of UPR activation was observed in the transgenic mouse model of tauopathy. No changes in the XBP-1 splicing or the level of p-eIF2a, BiP or CHOP was observed between tau P301S -expressing mice and wild type animals [18]. In our recent study, we confirmed the absence of UPR activation in the rTg4510 mouse model expressing tau P301L and we further expanded the UPR investigation to an in vitro model of tauopathy [19].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…) . Advantages associated with using the App KI strains have been described, with these mouse strains showing fewer artifactual anomalies compared with APP overexpressing mice . However, we did not observe NFT in the App KI mice during their lifespan, suggesting that the mice might also be useful as preclinical AD mouse models to investigate the pathological role of amyloidosis and amyloid‐associated neuroinflammation.…”
Section: Animal Models For Ad and Neuroinflammationmentioning
confidence: 66%
“…Additionally, enrichment of cholesterol in mitochondrial membranes is reported in AD pathology.Mitochondria from a mouse model of cholesterol overload exhibit increased susceptibility to Aβ-induced oxidative stress and consequent cytochrome c release(Fernandez, Llacuna, Fernandez-Checa, & Colell, 2009). Coupled with this observation, loading of mChol is increased in a mouse model of AD(Fernandez, Llacuna, Fernandez- Checa, & Colell, 2009), accompanied by an overexpression of the steroidogenic acute regulatory (StAR) protein(Barbero-Camps et al, 2014;Hashimoto et al, 2018). StAR is a lipoprotein that transports cholesterol from the ER to mitochondria, regulating the intra-organelle distribution of the lipid.…”
mentioning
confidence: 96%